Changer in the texture orientation of electrolytic nickel by cold air plasma - A. G. Anisovich; T. P. Urban; I. I. Filatova; A. S. Buynitskaya; S. V. Goncharik (Литьë и металлургия, 2020)
The effects of cold air plasma influence on the change in the microstructure, stress state and texture of the cathode nickel brand H-1 were studied. By the method of target metallography it has been established that the microstructure does not change under exposure to the cold air plasma. A decrease in the level of micro- and macrostress is shown. By the method of inverse pole figures it has been established that the pole density of the orientations (111), (200) and (311) decreases when exposed to plasma; orientation (311) changes the least intensively. The pole density of the orientation (220) increases from 4.42 in the initial state to 13.3 after plasma treatment, which means an increase in the electrolytic deposition texture. The causes of the observed effects are being discussed. It is assumed that the changes introduced by the plasma occur at a scale level that is much smaller than the size of the coherent scatter blocks.